Sistem Informasi Tracer Study Berbasis Web Menggunakan Konsep Restful AP Web Service pada SMK Negeri Karang Baru - Niswati, Za’imatun; Syukriansyah, Syukriansyah; Marlina, Dwi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
Vocational High Schools (SMK) aim to prepare graduates to be ready to enter the workforce or become enterpreneurs. To evaluate the quality of education and support the development of educational systems and mangement, tracer studies are essential. However, SMK Negeri 1 Karang baru does not yet have a tracer study application, resulting in alumni data being collected manually and inefficiently. Various studies have been conducted on the development of web-based tracer study applications in vocational high schools (SMK), but most still use conventional approaches and have not implemented RESTful API as a web service. Until now, no studies have been found that specifically develoved a web-based tracer study application using a RESTful API architecture to support system interroperability and flexibility. This study aims to develop a web-based tracer study application a RESTful API as the backend, in order to improve the efficiency of alumni data processing and facilitate cross-platform access. The implementation if focused on SMK Negeri 1Karang Baru as a case study.